Pengetahuan dan Perilaku Ibu Mengenai Pemberian Cairan Rehidrasi Oral Sebagai Penanganan Awal Diare Pada Anak - Tanzil, Keith William; Tirtasari, Silviana; Novendy, Novendy (Syntax Corporation, 2025)
Diarrhea remains one of the leading health problems among children worldwide, particularly in developing countries such as Indonesia. According to WHO and UNICEF data in 2024, diarrhea causes approximately 443,832 deaths annually in children under five years old. Appropriate early management, including the administration of oral rehydration solution (ORS) and zinc supplementation, has been proven to reduce mortality and prevent severe dehydration. One area with a high burden of diarrhea cases is the working area of Teluk Naga Public Health Center, Tangerang Regency. Given the role of mothers as the primary caregivers in families, their knowledge and practices regarding early management of diarrhea are crucial to preventing serious complications. This cross-sectional study aimed to assess mothers’ knowledge and practices related to ORS administration in early diarrhea management in children. A total of 72 respondents with children under 12 years old were selected using purposive non-random sampling. Data were collected using a questionnaire comprising six knowledge questions and five practice questions. The results showed that 48.6% of respondents recognized signs of dehydration, 58.3% knew ORS is the first-line treatment for diarrhea, and 41.7% knew zinc supplementation is required. Additionally, 19.4% kept ORS at home, while 52.8% would provide sugar-salt solution if ORS was unavailable. Mothers’ knowledge and practices regarding ORS use varied widely. Continuous health education and improved access to ORS and zinc are essential to enhance early diarrhea management in children.